Integration in a nurse practitioner‐led mental health service in rural Australia. (27th August 2015) - Barraclough, Frances; Longman, Jo; Barclay, Lesley
Abstract: Objective: Integration of mental health services is a prominent Australian mental health policy goal; however, there is little detail in the literature of how integrated mental health services are established or function. This study aimed to describe a nurse practitioner‐led primary healthcare rural mental health service and evidence of how the service was integrated with other services and the community. Design: This pragmatic exploratory study used case study methodology and analysed documents, quantitative data and qualitative data from individual and group semi‐structured interviews and a 'stakeholder meeting'. The study was part of a formal evaluation of this nurse practitioner service. Setting: Rural New South Wales. Participants: Twenty‐one service providers and stakeholders. Interventions: Introduction of a nurse practitioner led mental health service. Main outcome measures: Not applicable. Results: Purposely sampled participants were interviewed. Documentary evidence included briefing notes, minutes and progress reports and provided important background information. Non‐identifiable aggregated client data were analysed. Thematic analysis of the qualitative data produced a description of how and why the service was established, a description of the service and its impact and three analytic themes providing evidence of integration. Challenges to integrating this service are also discussed. Conclusions: The service was highly regarded. It addressed the drug and alcohol and mental health needs of a vulnerable rural community. The inception and implementation of the service were community driven, led by a number of agencies supported by a steering committee and underpinned by a Partnership Agreement. The service demonstrated key features of integration alongside experiencing challenges in optimising integration with acute mental health services.